Dependent interviewing: a framework and application to current research - Annette Jäckle (University of Essex, Institute for Social and Economic Research (ISER), 2006)
Panel surveys increasingly use dependent interviewing, where substantive answers from previous interviews are fed forward and used to tailor the wording and routing of questions or to include in-interview edit checks. The main reason for adopting dependent interviewing varies across survey organisations, surveys and items. As a result, a variety of dependent interviewing designs have been developed and comparisons of their effects are anything but straightforward. This article proposes a conceptual framework of the different design options and their effects, in an attempt to further the understanding of dependent interviewing. The framework is used to evaluate the effects of different designs in the Improving Survey Measurement of Income and Employment study. The article also clarifies the causes of longitudinal inconsistencies in repeated panel surveys (seam effects) and discusses the extent to which dependent interviewing can reduce these. The article ends with issues yet to be resolved.
Keywords: 330